The Last Tortilla : and Other Stories - Troncoso, Sergio, 1961- (Book collections on Project MUSE., 1999)
An anthology of stories on Mexican-Americans. One deals with the gulf between Anglo and Latin cultures, another is a romance between an older woman and a younger man, a third is on a boy's satisfaction with a job well done.